Supplementation of Carrageenan (Kappaphycus alvarezii) for Shrimp Diet to Improve Immune Response and Gene Expression of White Shrimp (Litopenaeus vannamei) - Ichoun Brawici Dhewang; Ervia Yudiati; Subagiyo Subagiyo; Rabia Alghazeer (Marine Science Department Diponegoro University, 2023)
White shrimp (Litopenaeus vannamei) is one of the leading commodities in aquaculture. In recent years, the shrimp farming industry worldwide has suffered heavy losses due to disease. Increasing the immune system in shrimp using immunostimulants that are more environmentally friendly such as carrageenan from Kappaphycus alvarezii, seems promising. The purpose of this study was to determine the increase in immune response and gene expression in White shrimp after carrageenan supplementary diet treatment. This research was using a laboratory-scale experimental method with a factorial Completely Randomized Design (CRD) which was analyzed using One Way ANOVA. The treatments were negative control (without carrageenan addition), 5 g.kg-1, 10 g.kg-1, 15 g.kg-1, and 20 g.kg-1 carrageenan supplemented feed. All treatments were replicated three times. 180 L. vannamei with average weight of 6.5±0.66 g is used for research object Total Haemocyte count (THC), Phenoloxidase (PO), Superoxide Dismutase (SOD) activity, and Phagocytic activity/Index (PA/PI) were examined after feeding the White shrimp with diets supplemented with carrageenan in time series sampling. Immune-related gene expression (Lipopolisaccharide Glucan Binding Protein/ LGBP, Pro Pehnol Oxidase/ ProPO, and Lectin Type C/ Lectin) was evaluated by quantitative Real-Time PCR (qRT-PCR) at the end of experiment. Results indicated that the immune parameters directly increased according to the doses of carrageenan and time. The 20 g.kg-1 carrageenan treatments gave better results. three immune-related genes expression i.e LGBP, Lectin, and proPO were upregulated. Therefore, carrageenan supplementation of shrimp feed can improve innate immunity as well as the expression of immune-related genes.